403. Study of early and late readmissions with COVID-19: A retrospective analysis. (31st December 2020) - Tariq, Zain; Vahia, Amit T; Grover, Kunal; Ignacio, Shalimar; Kaur, Ikjot; Talari, Goutham; Chaudhry, Zohra Sarfraz; Bhargava, Pallavi
Abstract: Background: Michigan was one of the severely impacted regions during the initial COVID-19 surge. An institutional protocol with early methylprednisolone (MP) to treat COVID-19 patients requiring supplemental oxygen was implemented. We sought to study characteristics of these patients who were readmitted with infectious and non-infectious diagnoses. Methods: A retrospective analysis of 21 COVID-19 readmitted patients initially admitted between 3/10/2020 and 4/20/2020 (early 0–7, late 8–30 days) was done. Total of 455 COVID-19 patients, confirmed by a positive nasopharyngeal RT-PCR were admitted during this time period. Demographic data, clinical characteristics, laboratory and radiographic results and treatments were compared among the early and late readmission groups. Univariate and logistic regression analysis were performed to study the risk factors associated with early readmission and worsening of COVID-19 pneumonia. Secondary analyses were performed comparing worsening COVID-19 pneumonia with other readmission diagnoses. Results: 4.6% (21/455) were readmitted, 14 early vs 7 late (median age 75 vs 65 yrs). Most early readmissions were COVID-19 related and 8 out of 14 had worsening COVID-19 pneumonia based on clinical picture, laboratory and imaging findings. Readmitted patients with worsening COVID-19 related pneumonia had significantly elevated CRP and lower ALC compared to last discharge value (Table 1). None of the late readmissions required MP. A total of 8 readmissions had bacterial coinfections (1/8 COVID-19 related) (Table 2). Bacterial infections unrelated to COVID-19 were aspiration pneumonia (2), urinary tract infection (2), enterococcal bacteremia from stercoral colitis (1), sacral osteomyelitis (1), and infected BKA stump (1). Each increasing day of MP duration during the first admission reduced the likelihood of early readmission by approximately 10% (OR 0.90, 95% CI 0.63–1.2, p=0.56) (Table 3). 1/14 and 0/7 patients died amongst early and late readmissions respectively. Table 1: Characteristics of early and late readmissions in COVID-19 patients Table 2: Readmission Diagnosis Table 3: Univariate and Multivariate Analysis of Readmissions Conclusion: Early MP in COVID-19 pneumonia was not associated with increased risk of early secondary bacterial infections in the readmitted patients. Optimal duration of MP in patients with COVID-19 pneumonia needs to be defined. Disclosures: All Authors : No reported disclosures